Analysis of The Role of Financial Management in Efforts to Increase Income of the SME Bunga Anggrek - Maria Krisanti Seuk; Nur Ida Iriani; Fendiyatmi Kusufa (International Research & Development for Human Beings (IRDH), 2026)
To analyze the role of financial management in increasing revenue at UKM Bunga Angrek Denis, with a focus on its contribution to better financial management and its impact on increasing business revenue. Qualitative approach with data collection techniques in the form of in-depth interviews, observation, and documentation. Qualitative approach with data collection techniques in the form of in-depth interviews, observation, and documentation. The data obtained were analyzed using qualitative data analysis techniques that include three main stages, namely data condensation, data presentation, and drawing conclusions. Data condensation is done to filter relevant information, data presentation aims to organize data so that it is easy to understand, and drawing conclusions is done to obtain the meaning and implications of the data that has been analyzed. The results of the study indicate that the financial management implemented by UKM Bunga Angrek Denis is quite effective even though it is still relatively simple. Positive practices such as regular bookkeeping, good cash management, and efficient use of capital have proven to be able to encourage increased business income. However, there are still several challenges faced, especially in terms of financial planning and supervision that still need to be improved so that potential income can be maximized. In addition, improving managerial skills in the financial sector is highly recommended to support future business growth and sustainability.